Equity policies in health plans: accessibility and something more? - Bran Barral Buceta; Ramón Bouzas Lorenzo; Andrés Cernadas Ramos; Ángela Fernández da Silva (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To examine the approach adopted by the health plans of the autonomous communities of Spain, verifying the weight given to the concept of equity; to detect referenced communities or situations, as well as to distinguish the perspective of approaching it, from access, equity or equalization. METHODS: Qualitative study, of content analysis using Nvivo12, carried out in 2020 on health plans in force since 2019 in the different regions (autonomous communities) of Spain. Sixteen current regional health plans were compiled to establish base categories (equity, accessibility and equality) and determine associated terms using Nvivo12, from which a content analysis was performed. RESULTS: The concept of equity is not emphasized in the regional health plans and its relevance is surpassed by the concepts of accessibility and equality. The use of these three concepts is associated with various categories indicating circumstances, conditions or groups to which the plans give greater attention. CONCLUSIONS: The results obtained coincide with previous studies on the contents and orientation of health plans, revealing a discrete presence of the concept of equity in the approaches adopted, although this does not undermine the alignment of health policies with the visions emanating from transnational organizations. It is detected the existence of a group to which special attention is given from the accessibility approach, the population with functional diversity.